Dualism of Body and Soul in the Ancient Arabic Criticism: A Textual Study - Salem, Rami Jamil (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to study philosophical dualism, which is the duality of soul and body that has evolved into a complex notion, encompassing both conceptual and practical aspects. The importance of the study lies in the fact that for Muslim and Greek philosophers, it was seen as purely philosophical. For Arab critics, the idea of dualism took a new form that emphasized the context and meaning of the word. Methods: The research followed the methodology of textual study، which is concerned with the study of dualism through texts in the relevant critical and rhetorical codes, which ensures the control of how it is expressed and represented. Results: The study findings are: 1. The pronounced presence of dualism in the realm of rhetoric and criticism. 2. The utilization of dualism by rhetoricians takes two forms. The first involves word-meaning representation, explicitly stated as analogous. Here, the word symbolizes the body, and meaning represents the soul. The second form is metaphorical, portraying the relationship as that of a dress and a beautiful lady. In this interpretation, the word is similar to clothing or a dress, while meaning is associated with a beautiful lady. Conclusions: The introduction of dualism into philosophical and rhetorical thought aligned with the characteristic of seeking antonyms. The philosophers' perspective on the relationship between the soul and the body closely matched that of the rhetoricians. In this framework, everything tangible was associated with the body, while everything morale was linked to the spirit and meaning.